2005
DOI: 10.1007/s11199-005-3713-y
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Application of the “Promiscuous Female” Stereotype and the Nature of the Application Domain: Influences on Sexual Harassment Judgments after Exposure to the Jerry Springer Show

Abstract: This study was designed to explore how the impact of exposure to a few stereotyped group members can be mediated by individual variation in stereotype application to other group members. When compared to participants exposed to nonpromiscuous women on an episode of the Jerry Springer Show, those exposed to promiscuous women perceived a victim of sexual harassment as less traumatized and more responsible for the event. In addition, exposure condition had no impact on judgments when the man physically touched th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Past research has shown that when sexual harassment involved a man touching a woman, ratings of the harassment tended to be uniformly high, whereas verbal harassment scores were affected by exposure to negative female stereotypes in the media (Ferguson et al, 2005). The scenario employed in our study (see Appendix) involved a male professor putting his hand on a female student's thigh.…”
Section: The Experimental and Control Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research has shown that when sexual harassment involved a man touching a woman, ratings of the harassment tended to be uniformly high, whereas verbal harassment scores were affected by exposure to negative female stereotypes in the media (Ferguson et al, 2005). The scenario employed in our study (see Appendix) involved a male professor putting his hand on a female student's thigh.…”
Section: The Experimental and Control Groupsmentioning
confidence: 99%
“…We also measured chronic exposure to video game violence and related this factor to sexual harassment judgments and rape-supportive attitudes. Ferguson et al (2005) noted ''there has been little empirical research on how the mass media might affect perceptions of sexual harassment" (p. 479). To add to this media effects literature, we designed our own instrument for the present study, which included a real-life account of sexual harassment between a college student and a professor and a series of judgments about this account.…”
Section: The Current Investigationmentioning
confidence: 99%
“…Moreover, endorsement of rape and sexual harassment myths is predictive of harassing behavior (e.g., Begany & Milburn, 2002;Diehl et al, 2012;Pryor, 1987). Yet, only a few studies to date have directly examined blame attribution in response to sexual harassment (De Judicibus & McCabe, 2001;Ferguson et al, 2005;Jensen & Gutek, 1982;Key & Ridge, 2011;ValentineFrench & Radtke, 1989). The available research has documented, in particular, that targets of sexual harassment are more likely to be blamed by employees rather than students (De Judicibus & McCabe, 2001), and by those holding more traditional sex role beliefs (Jensen & Gutek, 1982;Valentine-French & Radtke, 1989), and sexist attitudes (De Judicibus & McCabe, 2001).…”
Section: Moral Disengagement In Sexual Harassmentmentioning
confidence: 99%
“…After exposure to the sexual movie, male participants presented with a rape story thought that the victim enjoyed what happened to her. Ferguson et al (T. Ferguson et al, 2005) showed participants clips depicting either promiscuous or non-promiscuous women.…”
Section: Effects On Stereotypesmentioning
confidence: 99%